Performance of grassed swale as stormwater quantity control in lowland area - Mustaffa, Nurhazirah (2018)
Grassed swale is a vegetated open channel designed to attenuate stormwater through infiltration and conveying runoff into nearby water bodies, thus reduces peak flows and minimizes the causes of flood. UTHM is a flood-prone area due to located in lowland area, has high groundwater level and low infiltration rates. The aim of this study is to assess the performance of grassed swale as a stormwater quantity control in UTHM. Flow depths and velocities of swales were measured according to Six-Tenths Depth Method shortly after a rainfall event. Flow discharges of swales (QswaJc) were evaluated by MeanSection Method to determine the variations of Manning's roughness coefficients (ncalcula1e) that results between 0.075 -0.122 due to tall grass and irregularity of channels. Based on the values of Oswalc between sections of swales, the percentages of flow attenuation are up to 54%. As for the flow conveyance of swales, Oswalc were determined by Manning's equation that divided into Ocalculate, evaluated using ncalculatc, and Octesign, evaluated using roughness coefficient recommended by MSMA (nctesign), to compare with flow discharges of drainage areas (Qpcak), evaluated by Rational Method with 10-year ARI. Each site of study has shown Octcsign is greater than Qpeak up to 59%. However, Ocalculate is greater than Qpcak only at a ce1tain site of study up to 14%. The values of Octesign also greater than Ocalculate up to 52% where it shows that the roughness coefficients as considered in MSMA are providing a better performance of swale. This study also found that the characteristics of the studied swales are comparable to the design consideration by MSMA. Based on these findings, grassed swale has the potential in collecting, attenuating, and conveying stormwater, which suitable to be applied as one of the best management practices in preventing flash flood at UTHM campus.